EFFECT OF VERMICOMPOST KASCING PLUS AND ECO ENZYME APPLICATION ON THE GROWTH OF CLOVE SEEDLINGS UNDER NURSERY CONDITIONS - Ni Luh Kartini; Putu Oki Bimantara; Vanessa Vanessa; Trianita Br. Hutagalung; Querida Maria Grace; I Wayan Alit Rucika; Ivana Cein Pardosi; Manumpak Pardingotan Sitanggang; Ni Wayan Sri Anggarini; Rachel Maulidhya; Randa Simbolon; Yesika Manihuruk (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
The availability of healthy and vigorous seedlings is a crucial factor in supporting successful clove cultivation. This study aimed to evaluate the effect of vermicompost Kascing Plus combined with eco enzyme on the growth of clove seedlings under nursery conditions. The experiment was conducted using a randomized block design with nine treatments and three replications. Treatments consisted of different application rates of vermicompost Kascing Plus combined with eco enzyme, along with a urea fertilizer treatment as a comparison. Seedling growth was assessed based on plant height, stem diameter, and number of leaves, observed at two week intervals from two to ten weeks after planting. Selected soil chemical and biological properties, including organic carbon, total nitrogen, C over N ratio, microbial activity, and soil pH, were analyzed at the beginning and end of the experiment. The results showed that the combined application of vermicompost and eco enzyme significantly influenced clove seedling growth. Moderate application rates produced more balanced vegetative growth, reflected by higher plant height, thicker stems, and greater leaf numbers compared to the control treatment. Excessive application rates did not result in proportional growth improvement. These findings indicate that vermicompost Kascing Plus combined with eco enzyme can be utilized as an organic based fertilizer input to support clove seedling production and promote more sustainable nursery management practices in clove producing areas.